Correlation between pathoanatomic findings, imaging modalities, and genetic findings in patients with left ventricular hypertrabeculation/noncompaction. (3rd July 2021) - Stöllberger, Claudia; Finsterer, Josef
ABSTRACT: Introduction : Left ventricular hypertrabeculation, also named 'noncompaction' (LVHT) is a cardiac abnormality which is detected by pathoanatomic investigation or during cardiac surgery. Imaging techniques visualize LVHT by ventriculography, echocardiography, cardiac magnetic resonance imaging (CMRI) and computed tomography (CT). Areas covered : We aimed to assess 1) how often the definition of LVHT was validated against a criterion standard, 2) if inter- and intra-observer agreement was assessed, and 3) how often LVHT was associated with genetic diseases. A literature search disclosed 58 cases whose hearts were investigated pathoanatomically and by ≥1 imaging technique. Echocardiography was most frequently (95%) compared with pathoanatomy, followed by cMRI (31%), ventriculography (7%) and CT (5%). Intra- and inter-observer agreement was more frequently assessed for cMRI definitions and yielded more consistent results than for echocardiographic definitions. Since genetic findings were only reported from 4 of the 58 cases, no association with imaging findings could be carried out. Expert opinion : Correlation between pathoanatomic investigations with imaging techniques will hopefully contribute to reliable and uniformly accepted definitions of LVHT. Most probably, the echocardiographic definition of LVHT will be a synthesis of the currently used definitions, integrating short axis and four-chamber views. A refinement of cMRI definitions, considering pathoanatomic and echocardiographic investigations, seems necessary to avoid overdiagnosis.